TINJAUAN TENTANG KEKUATAN EKSEKUTORIAL SERTIFIKAT HAK TANGGUNGAN APABILA ADA PERLAWANAN DARI DEBITUR WANPRESTASI - Indra Prastika, I Putu; Pasek Diantha, I Made (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 02, Februari 2013)
Mortgage act is a guarantee letter on land for payment of certain debt which gives position primarily directed to certain creditor toward other creditors. Mortgage act is needed in relation to borrow from because it protects based on law both to the creditor and debtor. Due to the fact that this paper explains whether or not, mortgage has the executorial right, because of the certificate mortgage which has the same law strength with the statement of the court which already has firm statement of the court. Besides, this paper also explains about the strength of the mortgage when there is a challenge from debtor. So that when the debtor does not obey the agreement, the creditor does not need to propose the jerk to the court, but only to propose the application to the head court at place for doing the execution towards the guarantee letters which is given the burden. The method used in this paper was that normative method which referred to the law sources.
Keywords: Mortgage, Against agreement, Execution